ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN PERMASALAHAN INTEGRAL TAK TENTU - Siti Nurhikmah; Febrian Febrian (Jurnal Tatsqif, 2016)
This study displays an error analysis conducted on students’ answers towards the questions within the test on the topic of indefinite integral by using substitution method. This study aims at (1) analyzing error types undertaken by the students during accomplishing the questions, (2) deriving the percentage of each error type on the behalf of existing errors comparison, and (3) identifying the dominant error(s) for whole cases on the topic of indefinite integral by using substitution method to enable conclusion and reflection at the end of the study. The subject of the research is thirty students of 12nd graders of Science 1 of SMA Negeri 2 Tanjungpinang located in Basuki Rahmat Street, Tanjungpinang. This study is conducted by distributing sheets containing questions designed through the discussion and validation phases. The questions are in form of essay and there are 16 of them distributed into two groups of sheets (each group consists of eight questions). Based on the result of analysis by using Watson students’ error categorization, it is obtained that dominant percentage for error existing is 25% for inappropriate data. Others are 20.83% for inappropriate procedure, 18.75% for omitted data, 9.72% for omitted conclusion, 0.69% for response level conflict, 15.28% for undirected manipulation, 9.72% for skills hierarchy problem, and 0% for possible others found. This result concludes that the most frequent error existing is inappropriate data.